Supervised curricular internship in nursing in times of pandemic by Covid-19 in a Primary Health Care Unit in the interior of Amazonas (Research, Society and Development, 2021)
Objective: To describe the experience lived by undergraduate students in the nursing course in the midst of the pandemic by Covid-19, during the Supervised Curricular Internship (ECS) II discipline in a Basic Health Unit (UBS) of primary care in the interior of Amazonas. Method: This is an experience report, of a descriptive nature, about the experience of students from the 10th period of the nursing course. The internship took place from November 9 to December 18, 2020, in a UBS located in a municipality in the state of Amazonas. Results: The ECS was a great challenge for the students due to the risk of contagion with the new coronavirus, health education activities were carried out with a minimum of users and maintaining restrictive measures, the UBS received dozens of people daily with signs and symptoms similar to those of Covid-19, which led academics to perform health actions several times, clarifying the manifestations of flu-like syndromes, colds and the specifics of the new coronavirus. The participation of students in the Family Health Strategy (FHS) was essential, where they were able to contribute in meeting extra nursing demands, assisting in health actions for users and professionals of the unit, through lectures with relevant themes in times of pandemic. Final Considerations: The experience lived during the ECS in a health unit in the middle of the Covid-19 pandemic collaborated with the teaching and learning of students, adding new knowledge for professional and personal training.